2009
DOI: 10.1371/journal.pone.0006842
|View full text |Cite
|
Sign up to set email alerts
|

Navigation of Chemotactic Cells by Parallel Signaling to Pseudopod Persistence and Orientation

Abstract: The mechanism of chemotaxis is one of the most interesting issues in modern cell biology. Recent work shows that shallow chemoattractant gradients do not induce the generation of pseudopods, as has been predicted in many models. This poses the question of how else cells can steer towards chemoattractants. Here we use a new computational algorithm to analyze the extension of pseudopods by Dictyostelium cells. We show that a shallow gradient of cAMP induces a small bias in the direction of pseudopod extension, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
129
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 36 publications
17
129
0
Order By: Relevance
“…Chemotactic cells can also undergo spontaneous polarization and motility in the absence of an external gradient, likely because of activation by extracellular matrix components such as fibronectin (13,14). Observation of cells in 0-0 environments (C 0 = 0 nM, ΔC = 0 nM) revealed cells with frequent switching of orientation and very few cells that maintained persistence across the entire channel ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotactic cells can also undergo spontaneous polarization and motility in the absence of an external gradient, likely because of activation by extracellular matrix components such as fibronectin (13,14). Observation of cells in 0-0 environments (C 0 = 0 nM, ΔC = 0 nM) revealed cells with frequent switching of orientation and very few cells that maintained persistence across the entire channel ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the second case, the new pseudopodia start as very lean protrusions that dilate as soon as they include the cell body. Previous studies have shown that the angle between two splitting pseudopodia is approximately 55°and that very often a split to the right is followed by a split to the left and vice versa, which leads to a zig-zag trajectory (Bosgraaf and Van Haastert 2009a). On the contrary, pseudopodia that form de novo may protrude in any direction without any preference relative to the left or right previous or next pseudopod, which induces a random trajectory.…”
Section: Pseudopodia Characteristicsmentioning
confidence: 98%
“…Pseudopodia formation is triggered by different types of external signals: chemicals (chemotaxis) (Hoeller and Kay 2007;Weiner 2002) or temperature (thermotaxis) gradients, electric fields (Bahat and Eisenbach 2006;Zhao 2009), or surface heterogeneity (durotaxis). Such external cues may then control the time and the position at the cell boundary where the pseudopod will form, but growth time and length of the pseudopodia are instead independent properties of the false feet (Andrew and Insall 2007;Bosgraaf and Van Haastert 2009a;Karsenti 2008). In order to elucidate how the cell senses the external attractants, two models are generally used.…”
Section: Pseudopodia Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were biased to extend in the direction of their previous extension, which is consistent with the biological mechanism behind pseudopod formation [Bos09]. This was accomplished by calculating a motion vector derived from the difference between the center of mass of a cell before and after a stochastic step.…”
Section: Model Adaptationsmentioning
confidence: 97%